The safety and sustainability of bottle-pep therapy in pediatric patients with cystic fibrosis - GÖKDEMİR, YASEMİN (TAYLOR & FRANCIS INC, 2022)
Introduction Airway clearance techniques, which include positive expiratory pressure (PEP) devices, are essential in the pulmonary rehabilitation of cystic fibrosis (CF). Bottle-PEP is a low-cost but an effective alternative. Objective The aim of this study is to document the sustainability and safety of Bottle-PEP therapy as a home rehabilitation aid. Methods The study has been designed as a prospective case series. Patients with CF at the age of 6-18 years in acute exacerbation period were included in the study. Bottle-PEP training was given by a competent physiotherapist to those patients who did not use any method, and those who currently use another device were followed up with their existing devices. Thus, patients divided into two groups were followed up for 1 year. The patients were evaluated by phone every 2 weeks for exacerbation, regular and proper use of the device, and satisfaction during their follow-up. The patients were evaluated every 3 months with pulmonary function tests, 6-minute walking test (6MWT) and quality of life. Results Thirty-four patients were included in the study. The acute exacerbation score of the patients was 4.5 in the Bottle-PEP group and 6 in the other group, showing no significant difference (p = .1). Treatment compliance scores were compared, the median value of the Bottle-PEP group was 24 the other group was 27 and there was no significant difference (p = .6). During follow-up of, there were no significant differences in FEV1, 6MWT and quality of life data (p > .05). Conclusion Bottle-PEP treatment is not different from other devices in terms of long-term usability and safety in patients diagnosed with cystic fibrosis.
Keywords: Cystic fibrosis; positive expiratory pressure; rehabilitation; AIRWAY CLEARANCE; ADHERENCE; OSCILLATION; DESIGN